COMMUNITY EMPOWERMENT THROUGH THE MANUFACTURING OF LOCAL MICROORGANISMS FROM BANANA COMB WASTE AS A DECOMPOSER FOR PRODUCING LIQUID ORGANIC FERTILIZERS - Tisna Harmawan; Ulil Amna; Rahmawati (LPPM dan PM Universitas Samudra, 2022)
This Community Service Program aims to empower the community through the utilization of banana weevil waste in Matang Panyang Village, East Langsa. Based on the analysis of the situation in the village, there are many banana plants, both on vacant land and in resident’s house. The nature of the banana tree that only lasts for one harvest and then will be cut for plant the new one will of course be a problem for surrounding environment because so far the banana weevil has only been thrown away and cannot be used, so that it only becomes as a waste. This condition became the basis for the this program to carry out community service to utilize banana weevil waste to produce the liquid organic fertilizer. The partner in this program is resident of Desa Matang Panyang, who will be trained in making local microorganism from banana weevil waste as decomposers of liquid organic fertilizer.This program will be carried out in several stages: preparation, socialization, field practice, and monitoring. This program is expected to produce a productive and independent community as an effort to empower the community by utilizing surrounding waste. The expected output of this program is the existence of an independent community effort in innovating the use of banana weevil waste as a decomposer for making liquid organic fertilizer which can be used directly in improving the quality of the community's agriculture.